Evaluation of the efficacy and safety of single incision sling vs TVT-O in obese patients with stress urinary incontinence: Quality of life and sexual function analysis - Michele Carlo Schiavi; Valerio Carletti; Veronica Yacoub; Giorgia Cardella; Paolo Luffarelli; Herbert Carmelo Carlo Valensise; Pierluigi Palazzetti; Vincenzo Spina; Marzio Angelo Zullo (Elsevier, 2023)
Objectives: The aim of the study is to demonstrate the best stress urinary incontinence (SUI) surgical technique for women with a Body mass index higher than 30. The results of Transvaginal Tension Free Vaginal Tape-Obturator and Mini-sling surgery were analyzed and compared through both clinical examination and standardized questionnaires at 36 months of follow-up. Materials and methods: This is a retrospective multicenter study over 159 women with SUI who underwent surgery. Seventy-eight women underwent TVT-O and 81 Mini-sling technique. Intra and post-operative complications were recorded. Patients were monitored for 36 months by analyzing symptoms, voiding diary, quality of life and sexual activity through standardized questionnaires. Results: Complications had a low incidence in both groups and inter-group differences were superimposable. Only groin pain was statistically higher after TVT-O than after Mini-sling (12.8% vs1.2%, p = 0.03). At 36 months of follow-up, a statistically significant decrease in Positive stress test (%) and Q-Tip test (grade) was observed in both groups with no differences between them (p = 0.54 and p = 0.32 respectively). The mean number of daily voids was higher after TVT-O (p = 0.04) than after Altis (p = 0.22) with a significant difference in favor of the Altis group (p = 0.03). After 36 months, there were no significant differences between groups in terms of quality of life and sexual activity. PGI-I did not show any difference between groups (p = 0.21). Conclusion: TVT-O and Minisling had the same efficacy and results in the surgical treatment of SUI in obese women. Both techniques relieved their symptoms and improved their quality of life without any significant difference except for a lower incidence of post- Mini-sling complications.